(untitled) (Eurasian Medical Research Periodical, 2023)
The detection in the last decade of an intensive growth in the development of oncological diseases of the central nervous system among the population of the Fergana Valley and Andijan region in particular cannot be considered a bad sign due to the fact that this fact rather indicates an increase in the level of early diagnosis of pathological conditions of the body, rather than any pathogenic factors, including the influence of lifestyle, ecology or heredity. The ubiquitous and financially affordable appearance of neuroimaging diagnostic rooms allows not only to detect pathology in its very inception, but also to observe its course and control its development at almost any stage, including after radical surgical treatment